COMPARATIVE EVALUATION OF STAINLESS STEEL STENT (SIROLIMUS) AND COBALT CHROMIUM STENT (SIROLIMUS) IN PATIENT WITH CORONARY ARTERY DISEASE (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Coronary Artery Disease (CAD) occurs when the arteries of the heart that normally provide blood and oxygen to the heart are narrowed or even completely blocked due to clot formation. The Stenting implantation composes 84.2% of all Percutaneous coronary intervention (PCI). Despite the widespread use of these devices, bare metal stents (BMS) have been associated with a 20-30% restenosis rate which requires reintervention. In December 2006, US Food and Drug Administration cardiovascular experts concluded that for many patients, such as those with uncomplicated medical histories who undergo elective stenting of simple coronary blockages, drug-eluting stents remain a safe and appropriate therapy. Previously reports are suggestive of similar clinical outcomes for stainless steel and cobalt chromium bare metal stent. No reports are available for comparison of sirolimus eluting stainless steel stent and sirolimus eluting cobalt chromium stent. The present study was undertaken with the objective of comparative evaluation of Stainless Steel Stent (Sirolimus) and Cobalt Chromium Stent (Sirolimus) in Patient with Coronary Artery Disease. A single centric, retrospective, non-randomized study involving 118 patients who have undergone PCI from January 2011 to March 2012 implanted with either Sirolimus Stainless Steel Stent (SSSS) or Sirolimus Cobalt Chromium Stents (SCCS) were included in the study. Primary objective was to determine and compare the clinical outcome and rates of target vessel revascularization (TVR) in patients undergoing primary PCI for CAD patients who were treated with Sirolimus cobalt-chromium stents and Sirolimus stainless steel stents. The secondary outcomes of study were Major Adverse Cardiac Events, mortality at the end of 1 month, 6 month and 1 year of outcomes. At 1 month follow up there was no significant difference between two groups (p = 0.96). The individual clinical component showed no difference in occurrence of death (p = 0.29), MI (p = 0.29) and TLR (p = 0.96) at end of 6 month. The cumulative clinical outcome at 1 year rate of target vessel revascularization TVR (SSSS 1.75% versus SCCS 0%, p = 0.29), target lesion revascularization (SSSS 5.27% versus SCCS 1.63%, p = 0.27), and Major Adverse Cardiac Events (SSSS 22.80% versus SCCS 13.11%, p = 0.16). This study showed that among Coronary artery disease (CAD) patients undergoing primary percutaneous coronary intervention, sirolimus stainless steel stent showed similar efficacy and safety to sirolimus cobalt chromium stent.